Metabolic profiles from two different breakfast meals characterized by 1H NMR-based metabolomics. (15th September 2017) - Rådjursöga, Millie; Karlsson, Göran B.; Lindqvist, Helen M.; Pedersen, Anders; Persson, Cecilia; Pinto, Rui Climaco; Ellegård, Lars; Winkvist, Anna
Highlights: 1 H NMR metabolomics represents a tool to measure dietary exposure. Metabolic profiles from two breakfast meals were identified in healthy volunteers. Metabolites relating to breakfast type and beverage choice were identified. Intake of different meals can be traced in the metabolic profile of human urine. Abstract: It is challenging to measure dietary exposure with techniques that are both accurate and applicable to free-living individuals. We performed a cross-over intervention, with 24 healthy individuals, to capture the acute metabolic response of a cereal breakfast (CB) and an egg and ham breakfast (EHB). Fasting and postprandial urine samples were analyzed using 1 H nuclear magnetic resonance (NMR) spectroscopy and multivariate data analysis. Metabolic profiles were distinguished in relation to ingestion of either CB or EHB. Phosphocreatine/creatine and citrate were identified at higher concentrations after consumption of EHB. Beverage consumption (i.e., tea or coffee) could clearly be seen in the data. 2-furoylglycine and 5-hydroxymethyl-2-furoic acid – potential biomarkers for coffee consumption were identified at higher concentrations in coffee drinkers. Thus 1 H NMR urine metabolomics is applicable in the characterization of acute metabolic fingerprints from meal consumption and in the identification of metabolites that may serve as potential biomarkers.